Determinants of Social, Economic, and Academic Factors Influencing Pamulang University Students’ Decisions to Work While Studying - Sakarias Jesan (CV. Proaksara Global Transeduka, 2025)
This research is conducted in response to the increasing trend of university students undertaking employment while pursuing higher education as a strategy to meet financial needs and enhance career readiness. This study analyzes the factors influencing students’ decisions to work while studying, focusing on Regular CK (Thursday) class students at Pamulang University, South Tangerang. Using a quantitative descriptive approach, the research examines economic, motivational, social, and institutional factors shaping students’ dual roles as workers and learners.Data were collected through questionnaires and analyzed using several statistical procedures to ensure data quality. Validity testing confirmed that all research items were valid, while reliability testing showed strong internal consistency across variables (Cronbach’s Alpha > 0.70). Classical assumption tests were also performed, where the Kolmogorov–Smirnov test indicated normally distributed data (Asymp. Sig. = 0.200), and linearity testing confirmed significant linear relationships between variables.Correlation analysis revealed a strong positive relationship between the examined factors and students’ decisions to work while studying (r = 0.623, p < 0.05). Regression analysis further demonstrated that variable X significantly influences student decisions, supported by corrected item–total correlation values for X1.5 (0.485), X1.9 (0.484), X1.15 (0.516), X1.16 (0.502), and X1.18 (0.488), along with significant t-test and F-test results.The findings indicate that students’ decisions to work are influenced not only by economic necessity but also by personal motivation, career preparation, and social support. This study contributes theoretical insights into working-student behavior and offers practical implications for educational institutions and employers in developing supportive environments for students managing dual responsibilities.